Using Cooperative Learning to Increase Motivation (2023)
ABSTRACT: This action research was conducted at a public institution located in Medellín with 37 fifth graders between nine and 11 years old. It was aimed at exploring the effectiveness of cooperative learning to increase students’ motivation towards English learning. Data were collected through a motivation and interpersonal skills survey applied at two moments throughout the academic period, before and after the implementation of the project; a personal research journal in which I registered different situations and insights regarding the research process; video recordings that were useful to analyze the compliance of the research objectives; a focus group in which some students expressed their feelings and perceptions towards cooperative learning and its effect on motivation; and an interview with the CT to know her point of view regarding the strategy and the students’ level of motivation after the implementation of the project. Data analysis showed that there was some improvement in terms of positive interdependence and individual accountability among students, but not as expected. Collaborative learning was more evident than cooperative learning in this context, not only because grouping was more effective when students were allowed to choose their group instead of being assigned, but also because implementing roles and rewards proved to be ineffective. However, motivation did increase because of the activities proposed as evinced in some segments of the video recordings and what the students expressed in the focus group. Further research on cooperative learning should be more flexible considering that children are constantly changing and asking for novelty.